Kontribusi Psikologi Pendidikan dalam Penyusunan Sistem Pembelajaran yang Inklusif dan Adaptif: Studi Kasus di Madrasah Aliyah Nurul Iman Tarowang - Mardiana, Ainun; Hutamy, Ericha Tiara; Mahrany, Yunita; Saleh, Sirajuddin (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to explore the contribution of educational psychology in the development of an inclusive and adaptive learning system at Madrasah Aliyah Nurul Iman Tarowang, in order to meet the diverse learning needs of students. Using a qualitative approach with the case study method, data was collected through in-depth interviews with teachers, and observation of the learning process. The results show that teachers' understanding of educational psychology significantly plays a role in the application of learning strategies that are responsive to the diversity of students, where the principles of educational psychology, such as developmental theory and learning styles, are applied to adapt teaching methods and create a participatory learning environment. These findings indicate that teachers who integrate the principles of educational psychology are able to increase adaptability in learning through the adjustment of materials and evaluation methods that suit the needs of students. Further training on educational psychology is needed to strengthen teachers' capacity to deliver truly inclusive and adaptive learning, in order to support the overall academic and social development of students